The Mythical Double: The Representation of Eurydice in "Mercure" Amélie Nothomb’s novel - Marois, Laurence (Amaltea. Revista de Mitocrítica, 2011)
Amélie Nothomb‘s Mercure presents a multitude of intertextual references mostly derived from mythical, religious and literary “ grand narratives ”. Beyond simple punctual references, this story harks back to several founding myths of femininity. This article studies the influence that the character of Eurydice exerts on the novelist’s rewriting of these sources. The reprise of the myth of Orpheus and Eurydice is made thanks to the systematic application of the process of splitting the structure of the narrative and the elaboration of the feminine characters. It will be a question of understanding how, in the style of a “ palimpseste ”, Amélie Nothomb rewrites the myth of Orpheus and Eurydice and how the splitting process allows the author to transform the mythical figure of Eurydice.